2016
DOI: 10.1021/acs.jafc.6b04147
|View full text |Cite
|
Sign up to set email alerts
|

Niosomes Consisting of Tween-60 and Cholesterol Improve the Chemical Stability and Antioxidant Activity of (−)-Epigallocatechin Gallate under Intestinal Tract Conditions

Abstract: In order to improve the chemical stability and antioxidant activity of (-)-epigallocatechin gallate (EGCG) in the gastrointestinal tract, niosomes composed of Tween-60 and cholesterol were developed to encapsulate EGCG in this investigation. EGCG loaded niosomes with encapsulation efficiency around 76% exhibited a small Z-average diameter about 60 nm. Compared to free EGCG, the EGCG remaining in dialysis tubes was significantly improved for niosomes at pH 2 and 7.4. Meanwhile, the residual EGCG for niosomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Similar results were also reported by Liang et al. () who indicated that chemical stability and antioxidant activity of EGCG in SIF was preserved with niosomal encapsulation prepared using Tween‐60 and cholesterol.…”
Section: Modification Of Structure and Enhancement Of Egcg Stability supporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were also reported by Liang et al. () who indicated that chemical stability and antioxidant activity of EGCG in SIF was preserved with niosomal encapsulation prepared using Tween‐60 and cholesterol.…”
Section: Modification Of Structure and Enhancement Of Egcg Stability supporting
confidence: 90%
“…Although EGCG is the most abundant and biologically active compound in green tea (Barras et al., ), its poor stability in aqueous solutions (Istenic, Korosec, & Ulrih, ; Li et al., ; Li, Lim, & Kakuda, ; Puligundla, Mok, Ko, Liang, & Recharla, ) and poor solubility in fats and oils (Zhong & Shahidi, ) limits its direct addition to food products. Several carrier systems have consequently been developed to protect EGCG from degradation and to maintain its structural integrity (Bhushani, Karthik, & Anandharamakrishnan, ; Du, Zhou, Liu, Chen, & Li, ; Hu et al., ; Lante & Friso, ; Liang, Chen, Yokoyama, Williams, & Zhong, ; Paximada, Echegoyen, Koutinas, Mandala, & Lagaron, ; Puligundla et al., ; Ru, Yu, & Huang, ; Wang et al., ). Furthermore, the structure of EGCG has been modified to increase its lipophilicity (Zhong et al., ; Zhu et al., ).…”
Section: Modification Of Structure and Enhancement Of Egcg Stability mentioning
confidence: 99%
“…For instance, the stability of EGCG is readily influenced by environmental factors such as pH, temperature, and oxygen concentration. The encapsulated EGCG within a niosome (a vesicle consisting of tween 20 and cholesterol) shows better pharmacological as well as antioxidant properties . Most of the studies involving the gallic acid or gallates have been carried out on isolated cell cultures or in cell‐free systems, and therefore the problem of low absorption or metabolism have not been encountered.…”
Section: Increasing the Bioavailability Of Gallates Enhances Their Mementioning
confidence: 99%
“…The encapsulated EGCG within a niosome (a vesicle consisting of tween 20 and cholesterol) shows better pharmacological as well as antioxidant properties. [28] Most of the studies involving the gallic acid or gallates have been carried out on isolated cell cultures or in cell-free systems, and therefore the problem of low absorption or metabolism have not been encountered. On the other hand, in the in vivo animal models, the concentrations of supplemented gallates need to be kept on physiologically higher dosages to achieve a significant amount of tissue-level concentration, but this often elicits toxicity.…”
Section: Increasing the Bioavailability Of Gallates Enhances Their Mementioning
confidence: 99%
“…Simulated gastric and intestinal fluids (SGF and SIF) were prepared according to the previously reported method [21]. For preparation of SGF, water (1 L) was added to the mixture of HCl (7 ml, 37 wt %), NaCl (2 g) and pepsin (3.2 mg/mL).…”
Section: Stability Against Simulated Gastric and Intestinal Fluidsmentioning
confidence: 99%